DEVELOPMENT OF GROUP-BASED CAREER FISHING CHALLENGE MEDIA TO STRENGTHEN STUDENTS' CAREER UNDERSTANDING - Tryana Fauziyah; Yenti Arsini (Fakultas Keguruan Dan Ilmu Pendidikan Universaitas PGRI Banyuwangi, 2026)
Career understanding is one of the important aspects that need to be developed since elementary school. However, career guidance services in schools still tend to use lecture methods so that student involvement in understanding various types of work is not optimal. This research aims to develop group-based Fishing Challenge game media as a guidance and counseling service medium to strengthen the career understanding of elementary school students. The research uses the Research and Development method with a 4D model that is limited to the development stage . The research subjects consisted of one media expert, one material expert, one teacher, and 26 students in class V-A SD Al-Mukmin. Data collection techniques use observation, interviews, documentation, and questionnaires. Data were analyzed using a percentage descriptive technique. The results of the study showed that the analysis of media needs obtained a percentage of 93.08% with the category of being urgently needed. The results of the validation of media experts before the revision obtained a percentage of 74.2%, and after being reviewed, the results obtained a percentage of 100% and the validation of material experts obtained a percentage of 92.8% with a very feasible category. The results of the teacher's response obtained a percentage of 100% and the student's response obtained a percentage of 95.23% with the category of very practical. Thus, group-based Fishing Challenge game media is declared feasible and practical to be used in career guidance services in elementary schools. These findings show that interactive game media can be an innovative alternative to support strengthening students' career understanding from an early age.